Airline passengers’ screening: an appraisal from the Islamic law perspective - Adua, Ismail Mustapha; Hamid, Abdul Ghafur@Khin Maung Sein; Abdul Wahab, Mohammed Iqbal (International Islamic University Malaysia, 2015)
The alarming rate of aviation offences such as the offence of aircraft hijacking in the 21st century warrants the need to adopt various preventive and suppressive measures to prevent these offences. The current method to prevent and suppress these offences is to subject every passenger to screening of their body and baggage through the imaging technologies and physical searching called “pat down”, the purpose of which is to detect the presence of weapons, explosives and other dangerous materials that will aid the commission of any of these offences. As a sequel to the adoption of these methods, many queries have been raised especially from the human rights activists who argue that the so-called imaging technologies intrude on the fundamental human rights of passengers. While some passengers support the argument of the activists, others are in support of the aviation security practitioners. The question therefore is: what is the position of Islamic law on the screening of airline passengers using imaging technology? The present article intends to answer this question.